Global Considerations in Human Immunodeficiency Virus-Associated Respiratory Disease - Rylance, Jamie; Meghji, Jamilah; Miller, Robert F.; Ferrand, Rashida A. (Seminars in Respiratory and Critical Care Medicine, 2016)
Respiratory tract infection, particularly tuberculosis, is a major cause of mortality among human immunodeficiency virus (HIV)-infected individuals. Antiretroviral therapy (ART) has resulted in a dramatic increase in survival, although coverage of HIV treatment remains low in many parts of the world. There is a concurrent growing burden of chronic noninfectious respiratory disease as a result of increased survival. Many risk factors associated with the development of respiratory disease, such as cigarette smoking and intravenous drug use, are overrepresented among people living with HIV. In addition, there is emerging evidence that HIV infection may directly cause or accelerate the course of chronic lung disease. This review summarizes the clinical spectrum and epidemiology of respiratory tract infections and noninfectious pulmonary pathologies, and factors that explain the global variation in HIV-associated respiratory disease. The potential for enhancing diagnoses of noninfective chronic conditions through the use of clinical algorithms is discussed. We also consider issues in assessment and management of HIV-related respiratory disease in view of the increasing global scale up of ART.
Keywords: lung; HIV; respiratory tract Infection; chronic lung disease; developing countries; algorithms